Fracionamento, deglicosilação química, caracterização parcial e identificação de antígenos de Strongyloides venezuelensis aplicados no imunodiagnóstico da estrongiloidíase humana - Gonzaga, Henrique Tomaz (2015)
Strongyloides stercoralis, intestinal nematode parasite, infects millions of people. The cross-reactivity in immunodiagnosis is credited to antigenic complexity and glycoproteins. The aim of this study was to evaluate different heterologous antigenic fractions in human strongyloidiasis immunodiagnosis. Saline extract (SE) of infective larvae of S. venezuelensis was fractionated in ion exchange resin (diethylaminoethyl Sepharose - DEAE; fractions named DEAE S1 and DEAE S2 - which interacted with the resin) or gel filtration chromatography (Sephacryl S-100 resin) in F1, F2, F3 and F4. Larvae and SE were treated with sodium metaperiodate (MP) for chemical deglycosylation and verification of changes in carbohydrate content. SE and its fractions were evaluated in one-dimensional electrophoresis to characterize the proteic profile and were tested in serum samples [strongyloidiasis patients (G1), other parasitic infections (G2) and healthy individuals from an endemic area (G3)] for IgG detection and its subclasses by ELISA. Sensitivity (Se), specificity (Sp), area under curve (AUC), likelihood ratio (LR), intermediate range (IR) and valid range proportion (VRP) were calculated as diagnostic parameters. Protein identification by mass spectrometry was made after ELISA-IgG selection. B cell epitope prediction was performed. DEAE S1 and S2 showed protein profiles complementary to ES, with differential polypeptides (DEAE S1 - 21 to < 15 kDa; DEAE S2 - 21 to 50 kDa). DEAE S2 fraction presented higher diagnostic parameters for IgG detection (Se 92%, Sp 93%, AUC 0.981, LR+ 10.75, LR 0.09). Larvae showed distinct localization of carbohydrates and no carbohydrates were detected in SE after MPtreatment. Electrophoretic profiles of polypeptides were similar between SE before and after MP treatment. ELISA sensitivity reached 90 % for MP, Sp 94.6 %, LR+ 16.9, and LR 0.08. Significant interaction between IgG subclasses and extracts was observed for patients with strongyloidiasis (P = 0.02), i.e. reduction in detected levels. F2 gel filtration fraction showed bands of 13, 22, 25, 30, 33, 37, 45, 60, 70 and 140 kDa regions. IR and VRP values were better for ELISA-F2 (IR 23; VRP 98.9 %). ELISA index (EI) median in G1 was higher for SE when compared to F1-F4 fraction (P < 0.0001), however the F2 retained IgG-positive samples (94%). The EI reduction was accompanied by no detection of IgG positive samples in G2 and only F2 showed EI reduction in G3 compared to ES IE (t = 7.020, P < 0.0001). Bands 60 and approximately 33 kDa polypeptide regions from F2 were selected and excised for mass spectrometry analysis. Three homologous proteins of S. ratti were considered with reliable identification: aspartic protease 4 (ASP-4), 14-3-3 zeta and heat shock protein 60 (HSP60). It was concluded that: (1) DEAE fraction S2 was a sensitive and specific source of peptides for IgG detection in human strongyloidiasis diagnosis, (2) chemical deglycosylation overcome cross-reactivity in the control groups, demonstrating the role of carbohydrate residues in the recognition of anti-Strongyloides IgG and its subclasses and (3) F2 obtained after gel filtration, is composed of immunodominant proteins, which will allow definition of epitopes for vaccine protocols and diagnostic assays in human strongyloidiasis.